2000
DOI: 10.1677/jme.0.0250109
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide inhibits the enterochromaffin-like cell but not peroxisome proliferator-induced hypergastrinemia

Abstract: The peroxisome proliferator ciprofibrate induces hypergastrinemia and as a consequence, enterochromaffin-like (ECL) cell hyperplasia. The mechanism for the gastrin cell stimulation is unknown. The somatostatin analog octreotide LAR (long-acting release) was used to see if the stimulating effects of ciprofibrate could be attenuated. Female Fischer rats were dosed with ciprofibrate (50 mg/kg body weight per day) alone or combined with octreotide LAR (10 mg/30 days) for 60 days. Plasma gastrin and histamine, gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Normally, there is a reciprocal relationship between the activity of the antral G and D cells (6,76). During ciprofibrate dosing, we found a concomitant increase in gastrin and somatostatin mRNA abundance in the antral mucosa (3,70). To our knowledge, this had not been reported previously.…”
supporting
confidence: 46%
“…Normally, there is a reciprocal relationship between the activity of the antral G and D cells (6,76). During ciprofibrate dosing, we found a concomitant increase in gastrin and somatostatin mRNA abundance in the antral mucosa (3,70). To our knowledge, this had not been reported previously.…”
supporting
confidence: 46%
“…Finally, we found that gastric endocrine tumor regressed in three patients who had ZES and a family history of multiple type I endocrine neoplasia after long-term treatment with somatostatin analogs (Tomassetti et al 2000). The regression of the tumors was related to the decrease in serum gastrin levels and the hypothetic antiproliferative effect of somatostatin analogs on ECL-cells in both animals and humans , Bakke et al 2000, Tomassetti et al 2000, Erlandsen et al 2007). …”
Section: Discussionmentioning
confidence: 79%
“…Fischer rats were purchased from Møllegaard Breeding Center (Skensved, Denmark). Dosing of the animals with ciprofibrate was as described previously (5). Briefly, female Fischer rats (200-250 g) were given tap water (control group) or ciprofibrate (50 mg/kg body wt), by gastric intubation, once daily for 60 days.…”
Section: Methodsmentioning
confidence: 99%